Healthcare costs incurred by patients repeatedly referred to secondary medical care with medically unexplained symptoms: A cost of illness study - Burton, C; McGorm, K; Richardson, G; Weller, D; Sharpe, M (2012)
Background: Some patients are repeatedly referred from primary to secondary care with medically unexplained symptoms (MUS). We aimed to estimate the healthcare costs incurred by such referrals and to compare them with those incurred by other referred patients from the same defined primary care sample. Methods: Using a referral database and case note review, all adult patients aged less than 65. years, who had been referred to specialist medical services from one of five UK National Health Service primary care practices in a five-year period, were identified. They were placed in one of three groups: (i) repeatedly referred with MUS (N=276); (ii) infrequently referred (IRS, N=221), (iii) repeatedly referred with medically explained symptoms (N=230). Secondary care activities for each group (inpatient days, outpatient appointments, emergency department attendances and investigations) were identified from primary care records. The associated costs were allocated using summary data and the costs for each group compared. Results: Patients who had been repeatedly referred with MUS had higher mean inpatient, outpatient and emergency department costs than those infrequently referred (£3,539, 95% CI 1458 to 5621, £778 CI 705 to 852 and £99, CI 74 to 123 respectively. The mean overall costs were similar to those of patients who had been repeatedly referred with medically explained symptoms. Conclusions: The repeated referral of patients with MUS to secondary medical care incurs substantial healthcare costs. An alternative form of management that reduces such referrals offers potential cost savings. © 2011 Elsevier Inc.